2022
DOI: 10.1111/ajco.13767
|View full text |Cite
|
Sign up to set email alerts
|

Lag time to diagnosis as a predictor of mortality in children with extraocular retinoblastoma: Experience from a developing country

Abstract: Aim To define the prevalence of mortality and identify factors associated with mortality in pediatric patients with extraocular retinoblastoma attending the tertiary hospital in Indonesia. Methods We retrospectively collected medical records from 2013 to 2019 of patients who were diagnosed with extraocular retinoblastoma. Cox proportional hazard regression analysis with 95% confidence interval (CI) was used to evaluate the association of mortality predictors with patient outcomes (Hazard Ratio [HR], 95% CI) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Other studies have reported that a delayed diagnosis of retinoblastoma resulted in advanced disease upon presentation, with a higher likelihood of high-risk histological characteristics, a lower probability of globe salvage, and the requirement for adjuvant chemotherapy [12,[15][16][17] . In agreement with those previous studies, lag time was also shown to be significantly correlated with an increased mortality in retinoblastoma [18] . Although there were many studies that have already focused on lag time in retinoblastoma, investigations about this important concern in lower-middle income countries, including Indonesia, are limited.…”
Section: Introductionsupporting
confidence: 92%
“…Other studies have reported that a delayed diagnosis of retinoblastoma resulted in advanced disease upon presentation, with a higher likelihood of high-risk histological characteristics, a lower probability of globe salvage, and the requirement for adjuvant chemotherapy [12,[15][16][17] . In agreement with those previous studies, lag time was also shown to be significantly correlated with an increased mortality in retinoblastoma [18] . Although there were many studies that have already focused on lag time in retinoblastoma, investigations about this important concern in lower-middle income countries, including Indonesia, are limited.…”
Section: Introductionsupporting
confidence: 92%
“…Commonly described mutations are nonsense (56%), frameshift (12%), splice site changes (12%) and missense (12%). Exons 8,9,10,11,16,17,18,19,20,21,23 have been reported as frequent mutation carriers [9,10].…”
Section: Introductionmentioning
confidence: 99%